THE RISE OF EARLY MODERN SCIENCE : Islam, China, and the West - Huff, Toby E., 1942- (Cambridge University Press, 2017)
Now in its third edition, The Rise of Early Modern Science argues that to understand why modern science arose in the West it is essential to study not only the technical aspects of scientific thought but also the religious, legal and institutional arrangements that either opened the doors for enquiry, or restricted scientific investigations. Toby E. Huff explores how the newly invented universities of the twelfth and thirteenth centuries, and the European legal revolution, created a neutral space that gave birth to the scientific revolution. Including expanded comparative analysis of the European, Islamic and Chinese legal systems, Huff now responds to the debates of the last decade to explain why the Western world was set apart from other civilisations